Communication of da’wah diversity in digital screens on the Leonardo’s Youtube channel - Muchtar, Khoiruddin; Rustandi, Ridwan; Gunawan, Aji (Universitas Padjadjaran, 2023)
Background: This study examines the content of Leonardo’s YouTube channel titled “Journey of Religion: Habib Ja’far,” which focuses on presenting Islamic perspectives on diversity in Indonesia. The Islamic message is effectively conveyed through innovative means. Purpose: The objective of this study was to conduct an analysis of the messages pertaining to religious moderation as given by Habib Ja’far in the video. Methods: The study employed a qualitative methodology to conduct the research. The data were gathered through the application of Pierre Levy’s media theory, utilizing observation and analysis of literature and documentation. Results: The findings of this study indicate that social communication pertaining to religious tolerance is characterized by the integration of individuals through the utilization of new media platforms, such as the internet. Additionally, it was observed that Habib Ja’far’s delivery of religious messages is easily comprehensible. Furthermore, the central themes of his da’wah revolve around the concepts of the heart and love. Lastly, the contents of his da’wah can be categorized into distinct groups. Conclusion: The cultivation of religious tolerance can be facilitated by genuine and uncomplicated social encounters, bolstered by the utilization of contemporary communication platforms. Implications: The findings of this study suggest that the concept of religious moderation can be effectively communicated to younger generations through virtual platforms.